SELF EFFICACY MODEL AND CAREER DEVELOPMENT IN INCREASE EMPLOYEE ENGAGEMENT AND NURSE PERFORMANCE - Gede Pronajaya; Rina Anindita; Rian Adi Pamungkas (Dinasti International Journal of Education Management And Social Science, 2021)
One of the factors for the success of human resource management in an organization is employee performance. Organizations can be said to be successful when the performance of the organization's employees is good. The results of nursing audits are still low in one room, namely below 90%, the high rate of turnover that occurs in nurses every year, the influence of self-efficacy on the performance of nurses, and the level of clinical nurse IV are still small. The purpose of this study was to determine and analyze the effect of Self Efficacy and Career Development on Employee Engagement and Nurse Performance at Dharmais Cancer Hospital. The research sample consisted of 200 respondents. The design of this research is explanatory research of causality (explanatory research). The data analysis technique used the Three-Box Method and SEM (Structural Equation Model) with the AMOS 24 program. The results showed that self-efficacy and career development indirectly mediated by employee engagement had not affected nurse performance; employee engagement does not affect nurse performance; self-efficacy has a positive effect on nurse performance; career development does not affect nurse performance; Self-efficacy has a positive effect on employee engagement; Career development does not affect employee engagement. Research findings: nurse performance in the high category, self-efficacy in the high category, career development in the good category, and employee engagement variable in the engaged category. career development does not affect nurse performance; Self-efficacy has a positive effect on employee engagement; Career development does not affect employee engagement. Research findings: nurse performance in the high category, self-efficacy in the high category, career development in the good category, and employee engagement variable in the engaged category. career development does not affect nurse performance; Self-efficacy has a positive effect on employee engagement; Career development does not affect employee engagement. Research findings: nurse performance in the high category, self-efficacy in the high category, career development in the good category, and employee engagement variable in the engaged category.